2023
DOI: 10.1002/bdr2.2185
|View full text |Cite
|
Sign up to set email alerts
|

A putative adverse outcome network for neonatal mortality and lower birth weight in rodents: Applicability to per‐ and polyfluoroalkyl substances and relevance to human health

Abstract: Background Some per‐ and poly‐fluoroalkyl substances (PFAS) cause neonatal mortality and lower birth weight in rodents. We constructed an Adverse Outcome Pathway (AOP) network for neonatal mortality and lower birth weight in rodents, comprising three putative AOPs. We then assessed strengths of the evidence for the AOPs and applicability to PFAS. Finally, we considered the relevance of this AOP network to human health. Methods Literature searches targeted PFAS, peroxisome proliferator‐activated receptor (PPAR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 320 publications
0
2
0
Order By: Relevance
“…Peroxisome proliferator-activated receptor alpha (PPARα) is critical in regulating hepatic lipid metabolism, including fatty acid transport, esterification, and oxidation . As PFAS are organofluorine analogs of fatty acids (the endogenous ligand for PPARα), binding and activation of PPARα is a logical molecular-initiating event in lipid destruction . Most PFAS hepatic toxicity is thought to be mediated by PPARα, since PPARα knockout in mice reduces the outcomes of PFOS and GenX (an alternative PFAS substance) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxisome proliferator-activated receptor alpha (PPARα) is critical in regulating hepatic lipid metabolism, including fatty acid transport, esterification, and oxidation . As PFAS are organofluorine analogs of fatty acids (the endogenous ligand for PPARα), binding and activation of PPARα is a logical molecular-initiating event in lipid destruction . Most PFAS hepatic toxicity is thought to be mediated by PPARα, since PPARα knockout in mice reduces the outcomes of PFOS and GenX (an alternative PFAS substance) .…”
Section: Introductionmentioning
confidence: 99%
“…10 As PFAS are organofluorine analogs of fatty acids (the endogenous ligand for PPARα), binding and activation of PPARα is a logical molecular-initiating event in lipid destruction. 11 Most PFAS hepatic toxicity is thought to be mediated by PPARα, since PPARα knockout in mice reduces the outcomes of PFOS and GenX (an alternative PFAS substance). 12 In our previous study, through in vitro binding assays, we found that perfluoroalkyl carboxylates (PFCAs) and perfluoroalkyl sulfonates (PFSAs) with various numbers of perfluorinated carbons directly bind to human PPARα and that a variety of PFAS may induce adverse effects through PPARα in humans.…”
Section: Introductionmentioning
confidence: 99%